Forever Young? : Social Policies for a Changing Population in Southern Africa - Bruni, Lucilla Maria (World Bank, Washington, DC, 2016)
Demography affects our daily lives. Consciously or not, we take into account the demographic context when making choices on employment, savings, health, and education. This report studies how demographic change is likely to affect demand for social services in Southern Africa and how today’s policies can be shaped to reap potential benefits from demographic dynamics and address the population’s evolving needs. The authors define the social sectors as education, health, and social assistance and social policies as policies related to these three sectors. The study illustrates how social policies designed to fit with evolving demographic structures are likely to lead to wealthier and more productive future generations, fostering growth and equity. But the reverse also holds: ill-tailored social policies can hold back countries’ development and heighten intergenerational tensions. The rest of this report is structured as follows. Chapter two presents evidence on demographic trends in Southern Africa. Chapter three explains the report’s conceptual framework and how demography can be an opportunity or a curse, depending on the policy environment. Chapter four studies the five countries’ labor markets and documents challenges that a growing active labor force is likely to generate. Chapter five looks at the likely impacts of changing demographics on social sectors. It shows how a dependency ratio that will remain relatively low for decades to come will provide the opportunity to redirect social spending towards emerging priorities, and identifies which of these priorities will be in education, health, and social assistance. Chapter six concludes the study by discussing immediate policy implications.